Utilization of Fly Ash and Iron Slag in Concrete - An Experimental Study - Surendra, Cherukuru; S, Karthik; Raja Mohan K, Saravana (International Journal of Engineering and Technology, 2018)
The cement industry is responsible for about 6% of all CO2 emissions in the environment and numerous waste products out from the industries which is generating a lots of dumping problems and global warming. The main aim of this present study is to experimentally study the influence of partial replacement of cement with fly ash (FA) and partial replacement of fine aggregate with iron slag (IS) on the mechanical properties of concrete. Totally 10 mixes were prepared with 10, 20 and 30% replacements level of cement with fly ash and fine aggregate is replaced with 10, 20 and 30% by steel slag. The compressive and splitting tensile strength tests were found out after 7, 14, 28 and 7, 28 days age of curing for all the mixes respectively. Results were compared with conventional concrete and the optimum replacement percentage of FA and IS has reported.